Financial flows for regional integration - Griffith-Jones, Stephany (Institute of Development Studies. Univ. of Sussex BrightonGB, 1995)
Describes, analyses and evaluates the financial mechanisms explicitly created to support regional integration within Latin America and the Caribbean (LAC). Examines the scale and composition of intra-regional investment flows in the LAC Region and attempts to analyse their impact. Analyses the impact of regional integration on flows from outside the region, as well as their effects. Looks also at flows to Mexico.